Superoxide dismutase levels and peak expiratory flow in asthmatic children - Arie Kurniasih; Madarina Julia; Amalia Setyati (Indonesian Pediatric Society, 2015)
Background Asthma is a chronic inflammatory process which involve variety of cells such as inflammatory mediators, reactive oxygen species (ROS), and cytokines. The inflammatory process would be exacerbated in the presence of oxidative stress. Superoxide dismutase (SOD) is the first important enzyme to protect the respiratory tract against oxidative stress. The decreased of SOD has a correlation with increased of airway obstruction and bronchospasm. Objective To assess for a correlation between superoxide dismutase (SOD) levels and peak expiratory flow, as well as to determine the impact of SOD levels for predicting asthma attacks. Methods We conducted a prospective cohort study at Dr. Sardjito Hospital, Yogyakarta, between February and April 2011 involving asthmatic children aged 5-18 years. Subjectsâ€™ serum SOD levels and peak expiratory flow were measured at the same time point. We then performed a prospective study following up on the same subjects to find out if they had a recurrent asthma attack within one month of the tests. We also reassessed their peak expiratory flow one month after blood specimens were obtained. Results Thirty-nine patients were enrolled in this study. There was no significant correlation between SOD level and peak expiratory flow [r=0.289; 95%CI -0.025 to 0.47; P=0.074]. However, older age was significantly associated with higher peak expiratory flow (ô€‚=0.5; 95%CI 3.10 to 11.57; P=0.01). Lower levels of SOD increased the risk of asthma attacks in a month following the initial measurements (RR=5.5; 95%CI 1.6 to 18.9; P=0.009). Conclusion Superoxide dismutase (SOD) level is not significantly associated with peak expiratory flow. However, we find a relationship between older age and higher peak expiratory flow and a relationship between lower SOD levels and risk of asthma attacks within one month following the tests.